Quasi-static folding and deployment of rigidizable inflatable beams. (1st December 2021) - Wei, Jianzheng; Ding, Haixin; Chai, Yu; Eriksson, Anders; Tan, Huifeng
Highlights: A quasi-static model on restoring moment with deployment angle of an inflated beam is established. There are two phases during the quasi-static deployment process of an inflated slender beam. The contact force and buckling cross-section are studied by a deployable experiment. A theoretical model of restoring moment is verified by deployment of a rigidizable inflated beam. Abstract: This paper is concerned with a theoretical and experimental study of the deployment of inflated curved slender beams. A theoretical model for a beam with effects from restoring force and moment on deployment angle is proposed. Assuming slow deployment, a quasi-static viewpoint is utilized to simplify the model which the buckling cross-section is considered. The relation between deployment angle and contact area at the instability bending point is studied for the membrane chamber of a thermally rigidizable inflatable beam. While an inflated beam was constrained as simply-supported and fixed-free at its ends, the relations between the restoring force and moment and the internal pressure and its angle were tested by adding to the mechanical experimental method an infrared thermal imager. Results show that the restoring force and moment are increasing with the pressure at a given angle. Moreover, the restoring moment is nonlinearly related to the deployment angle. The correctness of the theoretical model was verified through experiments.